COVID-19 in older people with cognitive impairment in Latin America - Ibañez, Agustin Mariano (2020)
The current COVID-19 pandemic provides a unique opportunity to investigate the hypothesis that viral infections can precipitate neurodegeneration. Severe acute respiratory syndrome coronavirus 1 (SARSCoV-1), a pathogenic homolog of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), invades the brain through ACE2,1 and SARSCoV-2 might be neurotropic too. SARSCoV-2 also enters cells via the ACE2 receptor,1 which is widely expressed in the CNS, including in the striatum,2 where the virus might precipitate or accelerate neurodegeneration.